FACTORS AFFECTING PROCUREMENT PERFORMANCE IN THE INDUSTRIES AT BATAM - Immanuel Zai (Journal of Business Studies and Management Review, 2021)
The objective of this study is to examine factors affecting procurement performance in the industries at Batam. There are Information and communication technology, staff competence, and ethics are the most factors that affect procurement performance. This research model was tested using a non-purposing sample with survey data on 201 respondents who are directly related to procurement in industries at Batam. The results of this study support the proposed research model that information and communication technology, staff competence, and ethics have a significant positive effect on the procurement performance in the chosen industries at Batam. The studies also found that the application of information and communication technology in procurement had the greatest and most positive significant effect on improving procurement performance.